2019
DOI: 10.1055/s-0039-1693983
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Gastrostomy Tube Placement: Recognizing When Things Go Wrong

Abstract: Percutaneous radiologic gastrostomy is a commonly performed, minimally invasive procedure for long-term enteral access in patients with a variety of conditions. Compared with other methods, it is less invasive, less costly, and safe, with a high technical success rate. The risk of complications is low, and most require only conservative management. Early, accurate diagnosis of more severe complication is crucial, as these may require prompt intervention. Therefore, radiologists should understand the imaging fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The gastrostomy procedure was performed under general anesthesia during PEG tube replacement in 22.5% of the cases in 1 study, 27 but in most cases, the procedure is performed under conscious sedation with intravenous midazolam and/or fentanyl 28,29 . Recently, the procedure has been conducted under local anesthesia, and in our study, it was performed without sedation in all patients.…”
Section: Discussionmentioning
confidence: 74%
“…The gastrostomy procedure was performed under general anesthesia during PEG tube replacement in 22.5% of the cases in 1 study, 27 but in most cases, the procedure is performed under conscious sedation with intravenous midazolam and/or fentanyl 28,29 . Recently, the procedure has been conducted under local anesthesia, and in our study, it was performed without sedation in all patients.…”
Section: Discussionmentioning
confidence: 74%
“…Bleeding after gastrostomy is difficult to avoid, and reports suggest that approximately 1.4–2.5% of patients may experience injury to the inferior epigastric artery, resulting in iatrogenic pseudoaneurysm, rectus sheath hematoma, and wound oozing [ 20 , 21 ]. Although preoperative thin-slice enhanced CT can reveal the course of blood vessels in the rectus abdominis and intercostal areas [ 8 ], the incidence of bleeding in this study was slightly greater than that reported by Yasin et al [ 15 ]; however, the bleeding volume was lower, and all cases of bleeding were successfully managed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…There is likely underreporting of related adverse events. Compared with the relative frequency with which tubes are replaced, there is a low risk of complications, but early and accurate diagnosis of more severe complications is crucial, as prompt intervention may be required 25 …”
Section: Background (Available Knowledge)mentioning
confidence: 99%
“…Education to promote competency should be provided for those who replace G tubes with emphasis on the prevention of adverse events or early recognition of their occurrence. This should include knowledge of factors such as tract maturity, procedure, and tube type as well as patient condition 19,25 . Major principles including control of the replacement tube along the well‐formed gastrocutaneous tract, minimal insertion force during replacement and most importantly, reliable methods for confirmation of intragastric tube insertion should be significant factors in this education and competency training 16 …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation